Sequência didática para o ensino de funções afim, quadrática, exponencial e logarítmica - Bordin, Fabiana (2016)
This dissertation has objective to present an analysis of the results gotten through application of GeoGebra Educative Software in the teaching of Functions Relative, Quadratic, Exponential and Logarithmic. The study is classified as bibliographic, descriptive and quantitative. In chapter1 presents the historical approach to Mathematics, Algebra and Functions, besides the knowledge and importance of the teaching of Mathematics in High School and the applicability of GeoGebra Software in Functions teaching. In the chapter 2 presents the application of research and analysis of results. The activities of the teaching experience were applied to a Public Teaching School of High School in Frederico Wesphalen, Rio Grande do Sul, and the same occurred in five Thursdays, 3 hours each day, with a total of 15 hours/activity. With this study it was proved that the proper use of information and communication technology allows positive knowledge results, improve the teaching and learning of Mathematics.